Radiative neutron capture as a counting technique at pulsed spallation neutron sources: a review of current progress. (9th August 2016) - Schooneveld, E M; Pietropaolo, A; Andreani, C; Perelli Cippo, E; Rhodes, N J; Senesi, R; Tardocchi, M; Gorini, G
Abstract: Neutron scattering techniques are attracting an increasing interest from scientists in various research fields, ranging from physics and chemistry to biology and archaeometry. The success of these neutron scattering applications is stimulated by the development of higher performance instrumentation. The development of new techniques and concepts, including radiative capture based neutron detection, is therefore a key issue to be addressed. Radiative capture based neutron detectors utilize the emission of prompt gamma rays after neutron absorption in a suitable isotope and the detection of those gammas by a photon counter. They can be used as simple counters in the thermal region and (simultaneously) as energy selector and counters for neutrons in the eV energy region. Several years of extensive development have made eV neutron spectrometers operating in the so-called resonance detector spectrometer (RDS) configuration outperform their conventional counterparts. In fact, the VESUVIO spectrometer, a flagship instrument at ISIS serving a continuous user programme for eV inelastic neutron spectroscopy measurements, is operating in the RDS configuration since 2007. In this review, we discuss the physical mechanism underlying the RDS configuration and the development of associated instrumentation. A few successful neutron scattering experiments that utilize the radiative capture counting techniques will be presented together with the potential of this technique for thermal neutron diffraction measurements. We also outline possible improvements and future perspectives for radiative capture based neutron detectors in neutron scattering application at pulsed neutron sources.